Analisis Hukum Islam terhadap Praktek Jual Beli Online Tanpa Kepemilikan Barang (Drop Shipping) - Winario, Mohd; Kamalin, Muhammad (EL-EMIR Institute, 2025)
This study aims to analyze the practice of online buying and selling without ownership of goods (drop shipping) from the perspective of Islamic law. The main focus of this research is to assess the validity of contracts and ownership status in transactions conducted by business actors who do not directly own, control, or store the goods being sold. The research method used is qualitative with a normative-juridical approach, by reviewing secondary data in the form of classical and contemporary fiqh literature, fatwas of Islamic scholars, as well as regulations governing electronic commerce (e-commerce). The analytical technique used is descriptive-analytical, examining the compatibility of drop shipping practices with the principles of Islamic commercial law (muamalah). The results of the study indicate that drop shipping is permissible in Islam under certain key conditions, including transparency in the contract, absence of deceit or uncertainty (gharar), and the obligation of the seller to disclose that the product is shipped directly by a third party. If these conditions are met, the practice can be categorized as a valid wakalah bil ujrah or salam contract under Islamic law. Conversely, if there is any ambiguity or manipulation of information, the transaction may be considered impermissible (haram) or invalid.